Representation model of structured document for multilevel security - Mang SU; Feng-hua LI; Guo-zhen SHI; Li LI (Tongxin xuebao, 2012)
In order to solve the problem caused by the variety and openness of the network,the research for the models of structured document and access control were taken.A new structured document representation model and method for the security requirements of the multi-element access control and multi-level security was proposed,and corresponding structure of security attribute and example of extensible markup language (XML) was given.Finally,analyzed the security performance.